The case for the pharyngeal flap pharyngoplasty in the management of velopharyngeal dysfunction. Issue 9 (September 2022) - de Blacam, Catherine; O'Dwyer, Aisling; Oderoha, K. Ewomazino; Gilroy, Tanya C.; Duggan, Laura; Orr, David J.A.
Summary: Velopharyngeal dysfunction (VPD) occurs when there is inadequate closure of the velopharyngeal sphincter during speech. An incompetent velopharyngeal sphincter may require surgical intervention to create a functional seal between the oropharynx and the nasopharynx during speech. To date, no single pharyngoplasty procedure has emerged as superior to another, and the comparison of results between studies has been limited by variation in outcomes reporting. Here, we use the newly defined Core Outcome Set for VPD (COS-VPD) to report a consecutive series of 109 patients managed with a midline pharyngeal flap and simultaneous dissection and repositioning of the velar muscles. The overall 30-day postoperative complication rate was 3.6% (4 out of 109 patients). At 12-month follow-up, 79.3% of patients experienced a statistically significant improvement in hypernasality. Seven patients (6.4%) developed obstructive sleep apnoea (OSA) postoperatively, and this was confirmed with polysomnography, with four (3.6%) patients requiring takedown of the pharyngeal flap. Seven patients in total (7.3%) required takedown of the pharyngeal flap and sphincter pharyngoplasty because of insufficient improvement of their VPD following the initial procedure. Patient-reported outcomes were investigated using the Velopharyngeal Effects on Life Outcome (VELO) instrument, and a mean total score of 74.5 out of 100 was recorded. We conclude that cleft surgeons should not be dissuaded by historical concerns about high rates of perioperative complications and OSA and should consider including the pharyngeal flap in their armamentarium when managing patients with VPD.